Estudo das manifestações clínicas e hematológicas da doença falciforme subtipos SC e SD em crianças do Programa de Triagem Neonatal de Minas Gerais - Paulo do Val Rezende (2016)
Introduction and Objectives: The hemoglobin SC and SD are variants of sickle cell disease (SCD). The hemoglobinopathy SC is the second most common variant of SCD in the world, right after the SS genotype. Among the variants SD, SD-Punjab (HBB: c.364G> C; p.Glu121Gln) seems to be the most common subtype described in the literature, with higher prevalence in Northern India. Another variant is the HbS-Korle-Bu (HBB: c.220G> A; p.Asp73Asn), originally described in Ghana and whose clinical severity appears to be mild. The objectives of this study were to determine the prevalence and natural history of the hemoglobinopathy SC, and to characterize the molecular subtypes, to estimate the prevalence in Minas Gerais and describe the natural history of SD disease in newborns screened as part of the Neonatal Screening Program in the Brazilian state of Minas Gerais and treated at Hemominas Foundation. Methodology: Cohort of 21 infants with hemoglobinopathy SD and 461 with SC born between January 1999 and December 2012. The clinical, laboratory and genetic manifestations of the two entities were evaluated. Results: a) Hemoglobinopathy SC: 47.5% of 461 children were female; median age of 9.2 years. The mean values of blood tests were: hemoglobin 10.5 g/dL; reticulocytes 3,4%; white blood cell count 11,236/mm3; platelet count 337,098/mm3 and fetal Hb 6.3%. Clinical events: ASSC 14.8%, painful crises 74.6%, blood transfusion 23.4%, overt stroke 0.2%. Transcranial doppler was done in only 15.4% of the children. They were all normal if used the same current reference values for SS patients. Ten children used hydroxyurea, all with improvement of painful crises. Retinopathy was observed in 20.3% of 59 children who underwent ophthalmoscopy. Avascular necrosis was detected in 7 of 12 patients evaluated, predominantly in the left femur. Echocardiogram compatible with pulmonary hypertension was recorded in 4.6% of 130 children, with an estimated average systolic pulmonary artery pressure of 33.5 mm Hg. Co-inheritance of alpha thalassemia: 78 of 387 children (20.2%) had a deletion type -3.7. The risk of children without alpha thalassemia to present painful crises, infections, blood transfusions and ASSC was 1.7, 1.3, 2.9 and 15 times greater than in the group with alpha thalassemia co-inheritance, respectively. Statistically significant association was observed between alpha thalassemia coinheritanceand lower levels of MCV, MCH, reticulocyte count and white blood cell count. The mortality rate from all causes was 4.3%; b) Hemoglobinopathy SD: 11 children with SD-Punjab variant (1: 420,000;), 8 S-Korle-Bu (1: 480,000) and no other variant of HbD were identified. In 4 cases, samples for analysis were missing. Mean baseline data of SD-Punjab and S-KorleBu: hemoglobin 8.1 and 12.1 g/dL (p <0.001), white blood cell count 13,970 and 10,850/mm3 (p=0.02), platelet count 361,000 and 330,000/mm3 (p=0.4), reticulocytes 7.7 and 1.0% (p=0.002), fetal Hb 14.8 and 6.0% (p=0.02), HbS 45.1 and 50% (p=0.28), Hb D 36.3 and 41% (p=0.08); oxygen saturation 91.9 and 97% (p=0.002). Clinical events in the same order: acute splenic sequestration crises (ASSC) 2 vs 0; painful crises 8 vs 2; blood transfusion 5 vs 0; hydroxyurea because of repeated pain crises 3 vs 0. No transcranial Doppler (14 children) was abnormalConclusions: The severity of clinical manifestations in SC disease appears to be indeed less intense than in the SS form. However acute complications and organ damage may also occur with varying intensity. Early neonatal screening and systematic genetic study of alpha thalassemia co-inheritance can be useful for the follow-up of these patients and for family counseling about disease prognosis. The clinical course and blood cell counts of children with hemoglobin S/D-Punjab were very similar to those with hemoglobinopathy SS. In contrast, children with S-Korle Bu hemoglobin had clinical and laboratory course similar to those with sickle cell trait.